Measurement and comparison of rice production efficiency in Thailand and India: An efficient frontier approach - Duangthip Sirikanchanarak (2018)
© 2017 by the Mathematical Association of Thailand. All rights reserved. The main objective of this research is to measure production frontiers and technical efficiencies of a whole rice production in Thailand and India which are two of the major exporters in the global rice market. In addition, we attempt to investigate the development of technical efficiencies of rice productions in both countries between 2002 to 2014. Due to the limitation of the available time-series, an efficient frontier model (EFM) has been chosen because it is more efficient than the traditional stochastic frontier model (TSFM) in the case of small size of data both theoretically and practically. The results show that the EFM gives us better performances than the TSFM. Almost all inputs have positive relations with rice outputs as we expected. The considered factors of seed and pesticide have negative effects on Thailand and India’s rice outputs. Concerning the technical efficiency development, the experiment reveals that the technical efficiencies in utilizing resources of Thailand and India are in high level. Furthermore, the technical efficient score of India increased from 0.87 in 2002 to 0.98 in 2014 whereas that of Thailand decreased from 0.96 to 0.94 during the same period. Therefore, we conclude that India had more developments in technical efficiencies than Thailand. In a conclusion, we have policy recommendations of (1) increase more research on the usage of the inputs and the vocational trainings than those on the production scale in order to enhance the efficiencies in the production of rice, (2) provide the farmers on the financial access along with the financial education, and (3) implement zoning on the country-wide agricultures.